Adoção de crianças maiores e adolescentes: representações sociais de gestores escolares - Cruz, Solange Amália (2018)
This research has the aim to analyse the Social Representations of School Managers of eight schools, public and private, concerning the Older Children and Adolescent Adoption, revealing beliefs and myths created in the education area. We considered the theoretical methodological assumptions of the Social Psychology based on the Social Representations postulated by Serge Moscovici and his followers. In order to generate the information, we used interviews which were recorded and transcribed, and its contents were submitted to the analysis through the Analyse Lexicale par Context d’un Ensemble de Segments de Texte (ALCESTE) software. It was the results from this computational analysis, particularly, which were used for the lexical and content analysis. The analysis revealed that the managers suggest educational training about adoption focusing on the relevant legislation, as well as demonstrate beliefs considering that adopted children and adolescents tend to manifest behavioural problems in the schools. Another aspect approached by the managers is the concern about the revelation of the child adoption, one factor which may favour the improvement of the behaviour considered problematic. Most of all, we understand that the social representations derive from the little involvement with the topic and from the establishment of a common ideology without reflections that allow them to comprehend the directors, assistants and coordinators functions regarding the school team training for the better welcome of these students and their families. Therefore, we must inquiry if the adoption is segregated and if the school provide objective conditions in order to promote inclusion of the adopted students